2022
DOI: 10.20944/preprints202208.0379.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Milk Feeding for Septic Newborn Infants Might Minimize Their Exposure to Ventilation Therapy

Abstract: Background. It is well established that human milk feeding contributes in limiting lung disease among vulnerable neonates. The primary aim of this research was to compare the need for mechanical ventilation of human milk-fed sick neonates with that of formula-fed sick neonates. Methods. All late preterm and full term infants from a single center with findings of sepsis, from 2002 to 2017, were identified. Data regarding infant feeding during hospital admission were recorded. Multivariate logistic regression an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Previous studies have shown that the rate of breastfeeding initiation may be the same for infants admitted to the well-newborn nursery and the NICU and also that early cessation of breastfeeding is due to the newborn's sickness in less than 5% of cases (57). Hence, other authors have pointed to Moliner-Calderón et al 10.3389/fped.2023.1172799 links between feeding type and neonatal conditions that are rare during the first week of life, based on data similar to ours, despite the lack of detailed information on the periods in which their patients were fed HM (56). Third, we also had no information on the number of doses and the timeline of any vasopressor treatment.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Previous studies have shown that the rate of breastfeeding initiation may be the same for infants admitted to the well-newborn nursery and the NICU and also that early cessation of breastfeeding is due to the newborn's sickness in less than 5% of cases (57). Hence, other authors have pointed to Moliner-Calderón et al 10.3389/fped.2023.1172799 links between feeding type and neonatal conditions that are rare during the first week of life, based on data similar to ours, despite the lack of detailed information on the periods in which their patients were fed HM (56). Third, we also had no information on the number of doses and the timeline of any vasopressor treatment.…”
Section: Discussionsupporting
confidence: 55%
“…During the study period (2002-2017), 4,210 neonates were admitted to the participating NICU, 7.6% (n = 322; 260 in HM group and 62 in EF group) of whom met inclusion criteria and were eligible to participate in the final analysis. Similar to what was published in an earlier study of these cohorts examining the relationship between type of feeding and type of respiratory support (10), baseline characteristics of neonates who received any amount of HM and neonates who received only formula are summarized in Table 1. The mean age of newborns on admission to the neonatal unit was 4.3 days in cases of bacterial sepsis and 12.9 days in cases of viral sepsis, and 20% of infants with bacterial sepsis required vasoactive support compared to 2% of infants with viral sepsis.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation